Conservation and promotion of neglected and underutilized crop species in West Africa: Policy and governance - El Bilali, Hamid; Rokka, Susanna; Calabrese, Generosa; Borelli, Teresa; Grazioli, Francesca; Tietiambou, Sheirita Reine Fanta; Nanema, Jacques; Dan Guimbo, Iro; Dambo, Lawali; Nouhou, Bassirou; Gonnella, Maria; Acasto, Filippo (MDPI, 2024)
Neglected and underutilized crop species (NUCS/NUS) are claimed to contribute to sustainable development. However, many scholars argue that enabling policies and appropriate governance are needed to operationalize such a potential contribution. Therefore, this systematic review analyzes the literature dealing with the relationships between policy and governance aspects and the promotion of NUS in West Africa. It draws upon 45 eligible articles identified through a search conducted on the Web of Science in December 2023. The existing literature focuses on Nigeria and a few NUS, especially cassava. The addressed policy domains include biodiversity conservation; subsidies; seed systems; food security, self-sufficiency and sovereignty; trade and import substitution; food safety and health; climate change and energy; land use; research, innovation and development; and support and assistance systems. Meanwhile, the main governance domains are (1) inclusiveness and participation and (2) institutional capacity. The analysis suggests that NUS development is also affected by sectoral policy coherence and consistency as well as the policy–governance interplay. Future studies should widen the scope in terms of geographical coverage in West Africa and NUS addressed to allow for more comparisons. Furthermore, there is a need for further research to understand the synergies and trade-offs between sectoral policies affecting NUS promotion and development.